ТРАГИКА МУШКОГ У КОШТАНИ. - Копања, Јована М. (Journal for Languages & Literatures of the Faculty of Philosophy in Novi Sad / Zbornik za Jezike i Knjizevnosti Filozofskog Fakulteta u Novom Sadu, 2022)
In this paper, through the perspective of the male characters Mitka, Stojan, Hadži-Toma and Arsa, it is shown that in the patriarchal system neither men nor women are spared. The pressure based on social roles and the need to confirm themselves in the system lead to violent initiations with different fates, which is why they remain in the liminal phase -- "wounded and eager", emotionally damaged, deeply unhappy, in the gap between desires and possibilities. By placing heroes belonging to different generations in the same environment and facing the same temptation, heroes with and with different behavior, Stanković shows the inevitability of tragedy. Erotological analysis of behavior in relation to the object of desire distinguishes three different layers - awakened eros in Stojan, revived eros in Mitka and Hadži-Toma, and deeply suppressed eroticism in Arsa. Opposite all of them stands Koštana, who is an erotic temptation for everyone except Arsa. As such, Koštana appears as an antagonist whose appearance threatens the stability of the established order. The carnival atmosphere dominated by dance and song is the opposite of everyday life in which everyone is tied to a specific role.